Home Country - Ron Geatz (Symphony in the Flint Hills, 2015)
In northern Australia, a new generation helps to heal their homelands. Standing atop the red cliffs of Fish River Gorge in Australia’s Northern Territory, it’s difficult not to indulge in a fantasy of nature primordial. More than 100 feet below, fish are clearly visible in the crystalline water. Flocks of squawking white cockatoos soar through the riverine forest, and wallabies dart in and out of view.
Keywords: home; Australia; nature; animals; mammals; grass; grassland; savanna; landscape; wildlife; Aboriginal; indigenous; native; people; ecology; fire; burning; burn; dry season; control; life; rejuvenate; plants; habitat; shelter; food; livestock; farming; ranching